Consumer Perspectives on Arranging Circular Economy - Dr. Rafiq Mansoor,; Murad Ahmed,; Asma Imran,; Musferah Mehfooz, (Al-Qanṭara, 2024)
The transition to a circular economy (CE) is essential for achieving sustainability goals, as it promotes the reduction of waste and resource consumption. Understanding consumer perspectives is crucial for the effective implementation of circular practices. This study aims to explore consumer motivations, behaviors, and barriers regarding participation in circular economy practices, focusing on how these factors influence the adoption of sustainable consumption habits.In this study, we employed a non-probability convenience sampling method to collect data from 600 Romanian consumers from March to June 2024, resulting in a final sample of 582 respondents. An online survey, designed using E-survey and Google Forms, assessed consumer attitudes and behaviors regarding circular economy practices. Disseminated via social media, the survey targeted diverse demographic segments. Data collection was voluntary and anonymous, with responses validated using SPSS software. Analysis revealed significant correlations between environmental concern, positive attitudes toward circular products, and actual purchasing behaviors. Structural equation modeling indicated a strong model fit, underscoring the importance of consumer motivations in promoting engagement with circular economy initiatives. This research underscores the significance of consumer perspectives in fostering circular economy practices. It highlights the need for businesses to address barriers and leverage motivators to enhance consumer engagement. By understanding consumer motivations and behaviors, companies can tailor their strategies to effectively promote circularity, contributing to a more sustainable economic model.